1998
DOI: 10.1177/104063879801000201
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Viral Diarrhea Virus in the Ovaries of Cattle Acutely Infected with Bovine Viral Diarrhea Virus

Abstract: Abstract. Bovine viral diarrhea virus (BVDV) is recognized worldwide as a major cause of economic loss in cattle. Infection with BVDV can result in several clinical outcomes. However, the reproductive consequences may be the most important. Infertility, early embryonic death, abortion, and congenital anomalies have all been reported following acute infection with BVDV. The cause of infertility following acute BVDV infection is not known. BVDV has been isolated from the bovine ovary and has been associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 22 publications
5
17
0
Order By: Relevance
“…51 Oophoritis, characterized by the presence of virusinfected macrophages, was seen following acute infection of heifers. 66 Follicular growth in ovaries from acutely infected heifers was impaired during the 2 subsequent estrous cycles after acute infection. 65 …”
Section: Special Pathologymentioning
confidence: 99%
“…51 Oophoritis, characterized by the presence of virusinfected macrophages, was seen following acute infection of heifers. 66 Follicular growth in ovaries from acutely infected heifers was impaired during the 2 subsequent estrous cycles after acute infection. 65 …”
Section: Special Pathologymentioning
confidence: 99%
“…Ncp BVDVs are the prominent biotypes in the field and cause persistent infection, vital for transmission and survival of BVDV. BVDV infection in susceptible cattle can lead to either acute infection in immuno-competent animals, persistent infection in developing, immunologically naïve bovine fetus or a chronic infection within immune-privileged sites (testicular tissue, ovarian tissue and central nervous system's tissue) following transient infection (Voges et al, 1998;Grooms et al, 1998;Givens et al, 2003;Blas-Machado et al, 2004). Cattle with prolonged BVDV infection will develop a significant immune response accompanied by high neutralizing antibody titers (Voges et al, 1998;Givens et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Brownlie et al [5] determined the existence of BVDV Ag in all ovaries of PI heifers. Some researchers [16] explained that the BVD virus in acutely infected animals can cause infertility by affecting ovarian function. In this study, the CR of PI BVDV (Ag+/Ab-) heifers was found to be 53.85%, and that of uninfected animals was found to be 61.21%; no statistical significance was determined between the two groups.…”
Section: Discussionmentioning
confidence: 99%